2020
DOI: 10.1073/pnas.1915741117
|View full text |Cite
|
Sign up to set email alerts
|

Lower socioeconomic status and the acceleration of aging: An outcome-wide analysis

Abstract: Aging involves decline in a range of functional abilities and phenotypes, many of which are also associated with socioeconomic status (SES). Here we assessed whether lower SES is a determinant of the rate of decline over 8 y in six domains—physical capability, sensory function, physiological function, cognitive performance, emotional well-being, and social function—in a sample of 5,018 men and women aged 64.44 (SD 8.49) y on average at baseline. Wealth was used as the marker of SES, and all analyses co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(135 citation statements)
references
References 43 publications
12
118
1
4
Order By: Relevance
“…This link of depression and insomnia with financial hardship could be explained through some mechanisms, including financial strain, exposure to stressful, unsafe and unstable environments, reduced opportunity of education, low social support, and unhealthy lifestyle behaviors such as smoking, drinking, and obesity [ 2 , 8 , 9 ]. Another way of looking at this relationship is that less wealth has been associated with a faster decline in age-related functional abilities and phenotypes such as physical capability, sensory function, physiological function, cognitive performance, emotional well-being, and social function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This link of depression and insomnia with financial hardship could be explained through some mechanisms, including financial strain, exposure to stressful, unsafe and unstable environments, reduced opportunity of education, low social support, and unhealthy lifestyle behaviors such as smoking, drinking, and obesity [ 2 , 8 , 9 ]. Another way of looking at this relationship is that less wealth has been associated with a faster decline in age-related functional abilities and phenotypes such as physical capability, sensory function, physiological function, cognitive performance, emotional well-being, and social function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings lend support to studies on life course cognitive health. First, growing evidence shows independent associations between childhood SES and later-life cognitive function ( Fors et al, 2009 ; Kaplan et al, 2001 ; Luo & Waite, 2005 ; Marden et al, 2017 ; Nguyen et al, 2008 ) and cognitive decline ( Brown, 2010 ; Marden et al, 2017 ; Melrose et al, 2015 ; Steptoe & Zaninotto, 2020 ). Second, existing literature have also demonstrated the important role of child health and nutrition in determining both components of cognitive aging ( Kobayashi et al, 2017 ; Nguyen et al, 2008 ; Zhang et al, 2010 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In particular, the rate of cognitive decline often signals to individuals their potential cognitive problems that may promote timely diagnosis and treatment, while the level of cognitive deficit often determines the risk of being assessed cognitive impaired or even demented. The few studies that link childhood circumstances with later-life cognitive trajectories often provide inconsistent evidence: some shows that adverse childhood circumstances can lead to higher rates of cognitive decline ( Brown, 2010 ; Marden et al, 2017 ; Melrose et al, 2015 ; Steptoe & Zaninotto, 2020 ), while others offer contradictory evidence ( Barnes et al, 2012 ; Everson-Rose, 2003 ). Therefore, research on adverse childhood circumstances and cognitive aging is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, an observed between socioeconomic status and nutritional status, cognitive functions and functional status was found in the study conducted by Shahar et al in a group of 2237 older people in Malaysia. The study showed that older people with low socioeconomic status were at a higher risk of developing health problems [ 22 ], which, in turn, speeded up the aging process [ 23 ]. These discussed relations between sociodemographic data and care dependency belonged also to the aims of the study conducted by Dueñas et al in which widowed women living alone with a low level of education were found to be more care-dependent [ 24 ].…”
Section: Discussionmentioning
confidence: 99%